Predicting risk of upper gastrointestinal bleed and intracranial bleed with anticoagulants: cohort study to derive and validate the QBleed scores - Hippisley-Cox, Julia (BMJ Publishing Group Ltd., 2014)
Objective To develop and validate risk algorithms (QBleed) for estimating the absolute risk of upper gastrointestinal and intracranial bleed for patients with and without anticoagulation aged 21-99 years in primary care. Design Open cohort study using routinely collected data from general practice linked to hospital episode statistics data and mortality data during the five year study period between 1 January 2008 and 1 October 2013. Setting 565 general practices in England contributing to the national QResearch database to develop the algorithm and 188 different QResearch practices to validate the algorithm. All 753 general practices had data linked to hospital episode statistics and mortality data at individual patient level. Endpoint Gastrointestinal bleed and intracranial bleed recorded on either the linked mortality data or the linked hospital records. Participants We studied 4.4 million patients in the derivation cohort with 16.4 million person years of follow-up. During follow-up, 21 641 patients had an incident upper gastrointestinal bleed and 9040 had an intracranial bleed. For the validation cohort, we identified 1.4 million patients contributing over 4.9 million person years of follow-up. During follow-up, 6600 patients had an incident gastrointestinal bleed and 2820 had an intracranial bleed. We excluded patients without a valid Townsend score for deprivation and those prescribed anticoagulants in the 180 days before study entry. Risk factors Candidate variables recorded on the general practice computer system before entry to the cohort, including personal variables (age, sex, Townsend deprivation score, ethnicity), lifestyle variables (smoking, alcohol intake), chronic diseases, prescribed drugs, clinical values (body mass index, systolic blood pressure), and laboratory test results (haemoglobin, platelets). We also included previous bleed recorded before entry to the study. Results The final QBleed algorithms incorporated 21 variables. When applied to the validation cohort, the algorithms in women explained 40% of the variation for upper gastrointestinal bleed and 58% for intracranial bleed. The corresponding D statistics were 1.67 and 2.42. The receiver operating curve statistic values were 0.77 and 0.86. The sensitivity values for the top 10th of men and women at highest risk were 38% and 51%, respectively. There were similar results for men. Conclusion The QBleed algorithms provided valid measures of absolute risk of gastrointestinal and intracranial bleed in patients with and without anticoagulation as shown by the performance of the algorithms in a separate validation cohort. Further research is needed to evaluate the clinical outcomes and the cost effectiveness of using these algorithms in primary care.